Antécédents historiques des organisations: les confréries indigènes au Chiapas - Infante, María Dolores Palomo (Anthropologica, 2022)
I intend to analyse the importance the cofradias had for indigenous people in Chiapas during the colonial period. That relevance lead to the transformation of the whole cultural system of these groups. In this context, this institution acted as a means of resistance as well as a form of adaptation to the new socio-cultural circumstances. My interest is to bring out the processes which help to the incorporation of the cofradia to the original cultural corpus and the mechanisms which took part in that integration. I also focus on this institution as a model of organization which has been copied by many of present organizations in the state of Chiapas.